ANALISIS SKANDAL PENGADAAN CHROMEBOOK KEMENDIKBUDRISTEK DALAM PERSPEKTIF AKUNTABILITAS PUBLIK DAN INTEGRITAS ISLAMI - Natasya Perangin Angin; Syauqiyah Ramadani Asfa Sirait; Thalita Zahraini Dalimunthe; Nasirwan Nasirwan (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2026)
This study examines the Chromebook procurement scandal at the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) that took place between 2019-2022, with a total budget of 9.3 trillion rupiah, from the perspectives of public accountability and Islamic integrity. This incident is considered one of the largest corruption cases in the education sector in Indonesia, resulting in a financial loss to the state of 2.18 trillion rupiah. The method used was descriptive qualitative, involving library research and analysis of various academic sources. The research findings indicate that the failure of accountability in this case is systemic and occurs at various levels, encompassing the manipulation of technical specifications, undisclosed conflicts of interest, a lack of strong external oversight, and a weak culture of integrity among leadership. From an Islamic perspective, these violations contradict the principles of amanah, justice, transparency, and mas’uliyyah. This study proposes changes focused on enhancing oversight at various levels, establishing transparent procurement processes, strengthening reporting systems, instilling Islamic values of integrity within the bureaucracy, and implementing effective sanctions as a deterrent.